2006
DOI: 10.1038/sj.cdd.4402039
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy delays apoptotic death in breast cancer cells following DNA damage

Abstract: Early signaling in camptothecin-treated MCF-7 cells followed an intrinsic pathway, but death was delayed and late events exhibited few hallmarks of apoptosis. BH3-only proteins, such as Noxa, Puma and BimEL, were activated and localized to mitochondrial sites within 24 h following drug exposure. However, caspase activity was low and death was unaffected by caspase inhibition. Transmission electron micrographs showed the presence of large vacuoles in drug-treated cells. An autophagic survival response has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
322
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(358 citation statements)
references
References 37 publications
31
322
1
2
Order By: Relevance
“…17,18 A series of studies reported that chemotherapy induced-autophagy promotes the survival of some kinds of cancer cell lines. [19][20][21][22][23] These results suggest that autophagy might be involved in the development of chemotherapy resistance. But few studies on the relationship between autophagy and chemotherapy were reported, especially studies utilizing resistant cancer cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 84%
See 1 more Smart Citation
“…17,18 A series of studies reported that chemotherapy induced-autophagy promotes the survival of some kinds of cancer cell lines. [19][20][21][22][23] These results suggest that autophagy might be involved in the development of chemotherapy resistance. But few studies on the relationship between autophagy and chemotherapy were reported, especially studies utilizing resistant cancer cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 84%
“…Consistent with previous studies, we found that MMP was damaged within 24 h when MCF-7 cells were treated with EPI, whereas caspase-9 activity did not increase dramatically. 19,35,36 Accordingly, only a few cells underwent intrinsic apoptosis, and the cells exhibited caspase-independent death. Interestingly, MCF-7 cells underwent autophagy when treated with EPI.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that autophagy was enhanced by etoposide. The upregulation of autophagy by chemotherapeutic drugs has already been described [42][43][44][45][46][47]. Chemotherapyinduced autophagy may promote cell resistance against it.…”
Section: Discussionmentioning
confidence: 94%
“…Doxorubicin-induced DNA damage stimulates cytoprotective autophagy through a PARP-1-dependent pathway [48]. Similarly, cisplatin-induced autophagy delays apoptosis in renal tubular epithelial cells [45] and tamoxifen and camptothecin-induced autophagy increases MCF7 breast carcinoma cell line viability [42,46]. Examples of autophagic cell death in response to chemotherapy were also described.…”
Section: Discussionmentioning
confidence: 98%
“…Hypoxic AKT suppression was associated with a decrease in cell proliferation and induction of autophagy [59], playing an important role in enhancing cell viability in adverse conditions [60,61]. These observations show the plasticity of invasive and proliferative tumor states, which can be mediated by the convergence of hypoxia and MET signaling pathways.…”
Section: 2hif-related Transcriptional Activation Of Rtks: Met Axlmentioning
confidence: 76%